THE INVESTIGATION OF MODALITY AND ADJUNCT IN SPOKEN TEXT OF PROPOSING A GIRL USING WAIJEWA LANGUAGE BASED ON HALLIDAY’S SYSTEMIC FUNCTIONAL LINGUISTIC APPROACH - Magdalena Ngongo (University of Kuningan, 2021)
This paper is aimed to describe modality and adjunct in spoken text of proposing girl using Waijewa language. Modality refers to degrees of indeterminacy. It is to construe the region of uncertainty that lies between ‘yes’ and ‘no’. It refers not only to verb modal but also to modality idea. Thus, modality is manifested into two ways, namely modalization and modulation. The use modality grammar enables people to emphasize what can or cannot be done on what is ordered or offered. Data informing this study were from observation by recording oral texts of proposing a girl happened in Wewewa community. These data then were transcribed and analysed based on systemic functional grammar. The results showed that the use of modality was realized simultaneously by verb such as baka amiko-ngga dede wa kadanu … ‘I will come to take my handbag…’. The use of modality showed varieties of probabilities and obligation. Modalization tended to be uttered by bride’s party whereas modulation by groom’s party. This fact indicated interpersonal relationship in which groom’s party took a position as humble as possible in speaking and usually agreed everything stated or asked by bride’s parents. While bride’s party was dominant in speaking. This condition was influenced by honour value as one of the six values in this text. The use of adjunct related to mood adjunct that covered modal adjunct such as probability, usuality, obligation, obviousness, intensity, and polarity; and comment adjunct such as admissive, desiderative, entreaty, evaluative, opinion, predictive, persuasive, and presupposition.